2019
DOI: 10.1111/jocd.13089
|View full text |Cite
|
Sign up to set email alerts
|

Lifting vs volumizing—The difference in facial minimally invasive procedures when respecting the line of ligaments

Abstract: Background The arrangement of the facial soft tissue layers is different with respect to the line of ligaments: medially oblique and laterally in parallel. Aims This split‐face study was designed to investigate the effects on midfacial volumization if the same medial vs lateral injection points are targeted in various sequences. Methods Twelve patients (3 males, 9 females; 46.67 years ± 4.5) were included in this interventional study. On the right side of the face, lateral injection points were performed first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 18 publications
(20 reference statements)
4
75
0
4
Order By: Relevance
“…Slight influences were detected in all of the other scores except in the visibility of the lateral orbital rim. This evaluation reveals that the subdermal injection technique can induce aesthetic effects beyond the temple and into the lower face, which is confirmatory with previous publications 2,9 . From an anatomic perspective, this is conceivable as the product is injected superficial to the superficial temporal fascia and into the subdermal fatty layer with its respective superficial inferior temporal fat compartment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Slight influences were detected in all of the other scores except in the visibility of the lateral orbital rim. This evaluation reveals that the subdermal injection technique can induce aesthetic effects beyond the temple and into the lower face, which is confirmatory with previous publications 2,9 . From an anatomic perspective, this is conceivable as the product is injected superficial to the superficial temporal fascia and into the subdermal fatty layer with its respective superficial inferior temporal fat compartment.…”
Section: Discussionsupporting
confidence: 89%
“…The number of soft tissue filler injections performed is constantly increasing, as these procedures beget predictable aesthetic effects to ameliorate the signs of facial aging 1‐4 . The treatments are tailored based on patient's needs, aesthetic indication, anatomic region targeted, and product selected 5‐9 .…”
Section: Introductionmentioning
confidence: 99%
“…They argued that the lateral face injection preconditioned the ipsilateral midface for a more efficient injection‐related outcome. Another example was provided when injecting the midface lateral to the line of ligaments and targeting the infraorbital region in a second step 3 . Here, the authors reported a statistically significant repositioning of the midfacial soft tissues though they were not a priori targeted.…”
Section: Introductionmentioning
confidence: 96%
“…Recent research however has suggested that some areas of the face can influence other facial regions when specifically targeted, that is, an increase in local volume can influence soft tissue position of adjacent facial regions. Examples for these interesting biomechanical effects were provided by Casabona and colleagues 2,3 . In one of their studies, the authors injected soft tissue fillers to volumize the midface, on one side injecting lateral to the line of ligaments 3 before injecting medial, and on the contralateral side injecting medial prior to lateral.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation